Unified centralized/decentralized voltage and frequency control structure for microgrids - GODOY, Paulo Thiago de (2024)
The centralized secondary control strategies for microgrids (MG) are widely used due to their ease of control and coordination with distributed resources. However, the reliability of these strategies is extensively influenced by the communication system. To address the reliability issues associated with centralized control, this work proposes a novel Unified Secondary Control Structure (USCS). The USCS ensures regulation of the MG’s voltage and frequency even during communication or control failures. During normal operation, the USCS operates solely using the centralized control strategy, ensuring coordination with distributed resources. In case of communication system or centralized control failure, the USCS switches to the decentralized control strategy as a backup, ensuring voltage and frequency regulation. To facilitate the USCS voltage regulation, a novel decentralized voltage regulation strategy is proposed. This voltage control strategy is based on state estimation and equivalent systems. The proposed USCS and decentralized voltage strategy are implemented and tested on a benchmarkMGbased on the CIGRE residential European grid in Matlab/Simulink. The results demonstrate that the decentralized voltage strategy can effectively regulate MG voltage, and the USCS ensures voltage and frequency regulation even during failures, with a smooth transition between control modes even during communication delays. Additionally, a hardware-in-the-loop environment is employed to test the proposed USCS, where the centralized control is built in a real-time digital controller, and the MG system, converter controls, and decentralized controls are implemented in the Real Time Digital Simulator (RTDS) simulation environment. The results show that the proposed control structure can guarantee regulation even during failures and restore regular operation after failure. While the results are satisfactory, further development of a new gain-adjust strategy is necessary for the strategies operating in the USCS.